2016
DOI: 10.1108/oir-11-2015-0373
|View full text |Cite
|
Sign up to set email alerts
|

The influence of EWOM characteristics on online repurchase intention

Abstract: Purpose With the expansion of internet as a tool for exchanging information, companies include in their websites a virtual space to share information among users. The purpose of this paper is to explore the characteristics of consumers’ reviews (electronic word-of-mouth quantity, credibility and quality) as antecedents of customers’ online repurchase intentions. Specially, it proposes a model where trust on an online seller and perceived usefulness of a website mediate the influence of electronic word-of-mouth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
136
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(212 citation statements)
references
References 52 publications
14
136
0
16
Order By: Relevance
“…Seen handiness the impact of all EWOM qualities on online repurchase aim. EWOM believability and quality likewise in a roundabout way impact repurchase expectations through trust on the online merchant [16]. The discoveries affirm that lodging site quality impacts clients' apparent stream, which thusly, impacts their fulfilment and buy goal.…”
Section: Review Of Literaturementioning
confidence: 80%
“…Seen handiness the impact of all EWOM qualities on online repurchase aim. EWOM believability and quality likewise in a roundabout way impact repurchase expectations through trust on the online merchant [16]. The discoveries affirm that lodging site quality impacts clients' apparent stream, which thusly, impacts their fulfilment and buy goal.…”
Section: Review Of Literaturementioning
confidence: 80%
“…Some studies argue that consumers produce better attitudes and behaviors if there is a large volume of information on the website (Wang, Chou, Su, & Tsai, 2007). The higher the number of reviews, the more messages will be processed by users, which will result in a more positive inclination for future purchases (Matute, Polo-Redondo, & Utrillas, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study found that perceived ease of use had no significant direct effect on purchase intention. Although the perceived ease of use does not have a direct effect on purchase intention, the effect will be dominant when the customers' understanding coupled with the perceived ease (Matute, Jorge;Polo-Redondo, Yolanda;Ultrilla, 2016). A comprehensive understanding, both in terms of convenience (represent an aspect of perceived ease of use) and usability (represent an aspect of perceived usefulness), will further determine the decision to buy using e-commerce.…”
Section: **Significant Level At Alpha 1%mentioning
confidence: 99%